2011
DOI: 10.1186/1477-7525-9-83
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods used in assessing non-serious adverse drug events in observational studies among type 2 diabetes mellitus patients

Abstract: Clinical drug trials are often conducted in selective patient populations, with relatively small numbers of patients, and a short duration of follow-up. Observational studies are therefore important for collecting additional information on adverse drug events (ADEs). Currently, there is no guidance regarding the methodology for measuring ADEs in such studies. Our aim was to evaluate whether the methodology used to assess non-serious ADEs in observational studies is adequate for detecting these ADEs, and for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 89 publications
1
17
0
11
Order By: Relevance
“…The favourable safety profile of EPs 7630 is underlined by the fact that no SADRs were reported in this large patient population. AE rates under EPs 7630 were generally somewhat higher in randomised, controlled studies as compared to post-marketing surveillance and open outcomes studies, but this was to be expected which is in line with current literature surveys and reviews [41,42]. In the 19 double-blind, randomized, placebo-controlled trials covered by our review, AEs observed under EPs 7630 and placebo were similar with regard to type and incidence for the majority of system groups or symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…The favourable safety profile of EPs 7630 is underlined by the fact that no SADRs were reported in this large patient population. AE rates under EPs 7630 were generally somewhat higher in randomised, controlled studies as compared to post-marketing surveillance and open outcomes studies, but this was to be expected which is in line with current literature surveys and reviews [41,42]. In the 19 double-blind, randomized, placebo-controlled trials covered by our review, AEs observed under EPs 7630 and placebo were similar with regard to type and incidence for the majority of system groups or symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…The probability of drug-related symptoms occurring can be derived from the frequencies for the side effects as given in the SPCs. However, the information in the SPC is based on clinical trials in specific patient populations with a short follow-up period, and thus may differ from frequencies in clinical practice [37, 38]. These differences may explain why muscle pain in statin users is more frequently reported in clinical practice than that in the SPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Patient self-reports of adverse drug events (ADEs) are an important additional source of information on the safety of drugs because they differ from healthcare professional reports [2][3][4][5][6][7]. Healthcare professionals often underestimate symptomatic ADEs experienced by patients [7,8]. The added value of patient reports is acknowledged by the Food and Drug Administration (FDA) as well as the European Medicines Agency [9,10].…”
Section: Introductionmentioning
confidence: 99%